Assessment of missed opportunities for vaccination (MOV) in Burkina Faso using the World Health Organization's revised MOV strategy: Findings and strategic considerations to improve routine childhood immunization coverage. Issue 48 (10th November 2020) - Kaboré, Lassané; Meda, Bertrand; Médah, Isaie; Shendale, Stephanie; Nic Lochlainn, Laura; Sanderson, Colin; Ouattara, Mâ; Kaboré, William M.F.; Betsem, Edouard; Ogbuanu, Ikechukwu U.
Highlights: We assessed reasons for missed opportunities for vaccination (MOV) in Burkina Faso. We found the prevalence of MOV was 76% among all eligible children. The prevalence of MOV was 97% among children attending for a non-vaccination visit. Health workers' knowledge, attitude and practices were insufficient to minimize MOV. Reducing MOV can result in increases to both vaccine coverage and equity. Abstract: Background: Despite the remarkable achievements of the Expanded Programme on Immunization (EPI) in Burkina Faso, numerous challenges remain, including missed opportunities for vaccination (MOV) which occur when people visit a health facility with at least one vaccine due according to the national immunization schedule, are free of contraindications, and leave without receiving all due vaccine doses. In 2016, we used the revised World Health Organization's (WHO) MOV strategy to assess the extent of and reasons for MOV in Burkina Faso. Methods: We purposively selected 27 primary health facilities (PHFs) from the eight health districts with the highest absolute numbers of children who missed the first dose of measles-rubella (MR1) in 2015. We conducted exit interviews with caregivers of children aged 0–23 months, and requested health workers to complete a self-administered knowledge, attitudes and practices (KAP) questionnaire. Results: A total of 489 caregivers were interviewed, of which 411 were eligible for inclusion in our analysis. Medical consultation (35%) and vaccination (24.5%) were the most frequent reasons for visiting PHFs. Among the 73% of children eligible for vaccination, 76% of vaccination opportunities were missed. Among eligible children, the percentage with MOV was significantly higher in those aged ≥12 months and also in those attending for a reason other than vaccination. A total of 248 health workers completed the KAP questionnaire. Of these, 70% (n = 168/239) considered their knowledge on immunization to be insufficient or outdated; 83% failed to correctly identify valid contraindications to vaccination. Conclusion: Addressing MOV offers the potential for substantial increases in vaccine coverage and equity, and ultimately reducing the burden of vaccine-preventable diseases (VPDs). This will require the implementation of a series of interventions aimed at improving community knowledge and practices, raising health workers' awareness, and fostering the integration of immunization with other health services.